A Review of the Arcuate Structures in the Iberian Variscides; Constraints and Genetical Models - Dias, Rui (2016)
In the Iberian Variscides several first order arcuate structures have been considered. In spite of being highly studied their characterization, formation mechanisms and even existence is still debatable. Themain Ibero-Armorican Arc (IAA) is essentially defined by a predominantNW–SE trend in the Iberian branch and an E–Wtrend in the Brittany one. However, in northern Spain it presents a 180° rotation, sometimes known as the Cantabrian Arc (CA). The relation between both arcs is controversial, being considered either as a single arc due to one tectonic event, or as the result of a polyphasic process. According to the last assumption, there is a later arcuate structure (CA), overlapping a previousmajor one (IAA). Whatever themodels, they must be able to explain the presence of a Variscan sinistral transpression in Iberia and a dextral one in Armorica, and a deformation spanning from the Devonian to the Upper Carboniferous. Another arcuate structure, in continuity with the CA, the Central-Iberian Arc (CIA) was recently proposed mainly based upon on magnetic anomalies, geometry of major folds and Ordovician paleocurrents. The critical review of the structural, stratigraphic and geophysical data supports both the IAA and the CA, but as independent structures. However, the presence of a CIA is highly questionable and could not be supported. The complex strain pattern of the IAA and the CA could be explained by a Devonian — Carboniferous polyphasic indentation of a Gondwana promontory. In thismodel the CA is essentially a thin-skinned arc,while the IAA has a more complex and longer evolution that has led to a thick-skinned first order structure. Nevertheless, both arcs are essentially the result of a lithospheric bending process during the Iberian Variscides.